Elevating Organizational Performance of University through Organizational Learning, Organizational Agility, and Service Innovation - WANG, Jue; PHAWITPIRIYAKLITI, Chaithanaskorn; SANGSRIJAN, Jeeranan; TERASON , Sid (Journal of Ecohumanism, 2024)
With the development of recent decades, the quality and overall strength of Chinese universities have gradually improved. As comprehensive service-oriented organizations, universities can enhance their development level and overall image by improving organizational learning, organizational agility, and service innovation. To narrow the gap between local universities in Hainan and those in developed regions of China and the world, and to accelerate the process of building Hainan into an international education innovation island, this study examines the factors affecting the organizational performance of local universities in Hainan. This research explored the effects of organizational learning and organizational agility on organizational performance, and the mediating role of service innovation. A survey was conducted among 506 faculty members from five universities in Hainan. Structural equation modeling results showed that organizational learning significantly impacts organizational performance, organizational agility significantly impacts organizational performance, and service innovation plays a mediating role. The findings emphasize that organizational learning, organizational agility, and service innovation are crucial factors influencing organizational performance in universities. This study provides theoretical and practical insights for university managers to improve organizational performance. It suggests that universities should focus on the important role of organizational learning and agility in service innovation to further enhance organizational performance. With increasing competition in higher education globally, countries are putting higher demands on organizational innovation management. Building learning organizations, enhancing organizational agility, and optimizing service innovation are vital for improving university performance. The research findings offer valuable insights for studying factors affecting organizational performance development in universities.